The socioeconomic burden of spinal muscular atrophy in Saudi Arabia: a cross-sectional pilot study - Alotaibi, Khloud Mubark; Alsuhaibani, Mohannad; Al-Essa, Khalid S.; Bamaga, Ahmed Khamis; Mukhtar, Amnah S.; Alrumaih, Ali Mohammed; Al-Hasinah, Huda F.; Aldossary, Shaikhah; Alghamdi, Fouad; Temsah, Mohamad-Hani; Abanmy, Norah; Alwhaibi, Monira; et al. (Frontiers in Public Health, 2024)
Background Spinal muscular atrophy (SMA) is a rare debilitating condition with a significant burden for patients and society. However, little is known about how it affects Saudi Arabia's population. The socioeconomic and medical characteristics of affected SMA patients and their caregivers are lacking. Purpose This study aimed to describe the socioeconomic and medical characteristics of SMA patients and caregivers in Saudi Arabia. Patients and methods A cross-sectional questionnaire-based study was conducted using snowball sampling. Assessment tools including EuroQol (EQ-5D-5L) and visual analog scale (EQ-VAS), Generalized Anxiety Disorder 7-item (GAD-7), Patient Health Questionnaire (PHQ-9), and Costs for Patients Questionnaire (CoPaQ) were used to assess the quality of life (QoL), anxiety, depression, and out-of-pocket expenditures. Results Sixty-four caregivers of SMA patients participated. Type I patients had higher sibling concordance, ICU hospitalization, and mechanical support needs. Type III patients had better QoL. Type I patients' caregivers had higher depression scores. Type III patients' caregivers had higher out-of-pocket expenditures. Forty-eight percent received supportive care, while others received SMA approved therapies. Conclusion SMA imposes a significant socioeconomic burden on patients and caregivers, requiring more attention from the healthcare system. Access to innovative therapies varied across SMA types. Pre-marital screening and early detection are crucial to reduce disease incidence and ensure timely treatment.